Hospital services for acute care of elderly people - Coelho Filho, João Macedo (2000)
Although the implementation of geriatric services is an emerging priority in Brazil, little emphasis has been put on the type of acute care that should be provided for elderly patients in the hospital setting. The objective was to review some models of acute hospital care for elderly people, focusing on the role of geriatric medicine and its relationship with other specialities. Medline database (1989-1999), textbooks of geriatrics and gerontology, and other health publications were consulted in an attempt to identify all relevant publications about hospital services providing acute care to elderly people. The features of each model were compiled and discussed taking into account their suitability to the Brazilian health system. Some examples of interventions, with their effectiveness demonstrated by systematic reviews, were also mentioned. The models more frequently described were: long-time traditional, age-defined, unspecialized and integrated care. Variants of such models were frequently reported. There is no evidence pointing to one as the best model, but models favoring the integration of geriatrics with general medicine seemed to be particularly suitable to the Brazilian setting. With the aging of the population, there is a need to restructure the health services to face the increasing demands of elderly people. Given that the design of hospital services is an important factor for the effectiveness of geriatric care, this issue should be studied as priority in Brazil.